Young People's Perceptions of Europe in a Time of Change: IEA International Civic and Citizenship Education Study 2016 European Report - Losito, Bruno (Springer Nature, 2018)
Civic Education; ICCS; IEA Educational Achievement; Civic knowledge; Civics and citizenship; Attitudes to civic life; Engagement with civic life; Civic and Citizenship Education Study; ICCS 2016; Civic participation; European identity; Feelings of being European; Perceptions of freedom; Attitudes toward immigration; Freedom of European citizens; Perceptions of Europe and its future